A new objective histological scale for studying human photoaged skin. Issue 2 (25th June 2013) - Kawabata, K.; Kobayashi, M.; Kusaka‐Kikushima, A.; Akasaka, E.; Mabuchi, T.; Fukui, T.; Sugiyama, Y.; Takekoshi, S.; Miyasaka, M.; Ozawa, A.; Sakai, S.
<x xml:space="preserve">Abstract</x> Background A quantitative understanding of the histological alteration of the skin is important for assessing the severity of photoaging. Methods We performed Elastica‐van Gieson staining and immunohistochemistry for decorin on 34 facial skin sections. We evaluated the alteration of collagen fibers and decorin (a modulator for collagen fibrillogenesis), according to the 5 grades of morphological change in elastic fibers that was established by Kligman (1969). The objectivity of a stage (Stages I–VI), which was established in this study, was evaluated using weighted kappa statistical analysis based on the degree of agreement in stage determination by 11 observers using a blind procedure. Correlation between the crow's‐feet‐area wrinkles grades of another 26 women and stages was also analyzed. Results The initial alteration of elastic fibers was observed in the deep dermis. Decorin was not detected in very severely altered skin. Based on the combination of changes in the elastic fibers, collagenic fibers, and decorin, skin tissues were categorized into 6 stages according to severity. The statistical analysis showed almost perfect agreement between observers. Significant positive correlation between stages and wrinkle scores was found. Conclusions We propose a new objective histological scale that is useful for assessing the severity of photoaging.